The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/0104-9224/si25.04
|View full text |Cite
|
Sign up to set email alerts
|

Influência do Aporte Térmico sobre as Características e Propriedades de Cordões de Solda dos Aços AISI 316 e AISI 316L

Abstract: Resumo: Aços AISI 316 e AISI 316L possuem ampla aplicação industrial, por isso a importância de avaliar a soldabilidade dessas ligas. Neste estudo, foi feita análise comparativa entre as amostras de ambos os aços soldados com aportes de 0,5, 1,5 e 2,5 kJ/mm utilizando processo TIG autógeno. Foi analisada a variação do aporte térmico sobre a morfologia do cordão de solda, o espaçamento entre ferritas δ, a fração volumétrica de ferrita δ e a microdureza na zona fundida. Os resultados mostraram que as dimensões d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Through an analysis of the loads on the fitting under working conditions, the stress on the seal weld of the fitting under working conditions was captured, as depicted in Figure 4. The fitting was subjected to liquefied natural gas pressure, and, concurrently, the temperature stress at the weld was created by the existence of a temperature difference between the inner and outer walls [23,24]. These two types of loads interacted to affect the fitting's sealing performance.…”
Section: Model Of the Fitting Seal Structurementioning
confidence: 99%
“…Through an analysis of the loads on the fitting under working conditions, the stress on the seal weld of the fitting under working conditions was captured, as depicted in Figure 4. The fitting was subjected to liquefied natural gas pressure, and, concurrently, the temperature stress at the weld was created by the existence of a temperature difference between the inner and outer walls [23,24]. These two types of loads interacted to affect the fitting's sealing performance.…”
Section: Model Of the Fitting Seal Structurementioning
confidence: 99%
“…This increases the dendrite spacing and decreases the δ ferrite fraction since, according to Lippold and Kotecki [26], the austenite that forms during solidification consumes part of the ferrite. A study developed by Silva et al [30] had already shown that when welding AISI 316L steel using the autogenous GTAW method, the dendrite spacing increases according to the increase in heat input. In this study, it is observed that the same is valid for dissimilar welding.…”
Section: Analysis Of Welded Samplesmentioning
confidence: 99%